Analysis of the concentration of heavy metals and their vehicle emission in urban road dust of Kathmandu valley - Bikram Kumar Das,; Ram Kumar Sharma,; Madhav Narayan Shrestha,; Basant Lekhak, (Journal of Innovations in Engineering Education, 2024)
Greater environmental harm and health risks are associated with fine urban dust than with coarser urban dust. This study aims to analyze the heavy metal (Cu, Zn and Cd) concentration of heavy traffic road sections and compares it with medium traffic road sections with the same starting and end point for a study of how heavy metals from vehicles contribute to road dust (size